(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Let be a simple graph. A dominating set is a strong split dominating set if the induced subgraph is totally disconnected with at least two vertices. Let be the family of strong split dominating sets of of cardinality and . We define the strong split domination polynomial of a graph of order as the polynomial . In this paper, we determine the strong split domination polynomial of paths and obtain some of its properties.